Relative comparison of tissue specific bioaccumulation and radiation dose estimation in marine and freshwater bivalve molluscs following exposure to phosphorus-32. (December 2018) - Vernon, Emily L.; Smith, Jim T.; Jha, Awadhesh N.
Abstract: With respect to environmental protection, understanding radionuclide bioconcentration is necessary to relate exposure to radiation dose and hence to biological responses. Few studies are available on tissue specific accumulation of short-lived radionuclides in aquatic invertebrates. Short-lived radionuclides such as 32 Phosphorus ( 32 P), although occurring in small quantities in the environment, are capable of concentrating in the biota, especially if they are chronically exposed. In this study, we firstly compared tissue specific bioaccumulation and release (depuration) of 32 P in adult marine ( Mytilus galloprovincialis, MG) and freshwater bivalve molluscs ( Dreissena polymorpha, DP). Secondly, using the Environmental Risk from Ionising Contaminants Assessment and Management (ERICA) tool, we calculated tissue specific doses following determination of radionuclide concentration. Marine and freshwater bivalves were exposed for 10 days to varying 32 P concentrations to acquire desired whole body average dose rates of 0.10, 1.0 and 10 mGy d −1 . Dose rates encompass a screening dose rate value of 10 μGy h −1 (0.24 mGy d −1 ), in accordance with the ERICA tool. This study is the first to relate tissue specific uptake and release (via excretion) of 32 P from two anatomically similar bivalve species. Results showed highly tissue specific accumulation of this radionuclide and similarity of accumulation pattern between the two species. Our data, which highlights preferential 32 P accumulation in specific tissues such as digestive gland, demonstrates that in some cases, tissue-specific dose rates may be required to fully evaluate the potential effects of radiation exposure on non-human biota. Differential sensitivity between biological tissues could result in detrimental biological responses at levels presumed to be acceptable when adopting a 'whole-body' approach. Highlights: 32 P accumulation and depuration studied in two bivalve species. 32 P showed a concentration dependant uptake in bivalves. Tissue specificity evident, independent of species. Digestive gland showed the highest 32 P bioaccumulation. Tissue specific dose rates in some cases significantly higher than whole-body averages.